Phenotypic and Clonal Stability of Antigen-Inexperienced Memory-like T Cells across the Genetic Background, Hygienic Status, and Aging - Moudra, Alena; Niederlova, Veronika; Novotny, Jiri; Schmiedova, Lucie; Kubovciak, Jan; Matejkova, Tereza; Drobek, Ales; Pribikova, Michaela; Stopkova, Romana; Cizkova, Dagmar; Neuwirth, Ales; Michalik, Juraj; et al. (The Journal of immunology, 2021)
Ag-inexperienced memory-like T (AIMT) cells are functionally unique T cells, representing one of the two largest subsets of murine CD8+ T cells. However, differences between laboratory inbred strains, insufficient data from germ-free mice, a complete lack of data from feral mice, and an unclear relationship between AIMT cells formation during aging represent major barriers for better understanding of their biology. We performed a thorough characterization of AIMT cells from mice of different genetic background, age, and hygienic status by flow cytometry and multiomics approaches, including analyses of gene expression, TCR repertoire, and microbial colonization. Our data showed that AIMT cells are steadily present in mice, independent of their genetic background and hygienic status. Despite differences in their gene expression profiles, young and aged AIMT cells originate from identical clones. We identified that CD122 discriminates two major subsets of AIMT cells in a strain-independent manner. Whereas thymic CD122LOW AIMT cells (innate memory) prevail only in young animals with high thymic IL-4 production, peripheral CD122HIGH AIMT cells (virtual memory) dominate in aged mice. Cohousing with feral mice changed the bacterial colonization of laboratory strains but had only minimal effects on the CD8+ T cell compartment, including AIMT cells.
Keywords: Immunologic Memory; myši; Animals; Antigens; Clonal Evolution; nestabilita genomu; Mice, Transgenic; myši transgenní; Phenotype; stárnutí; myši inbrední C57BL; Mice, Inbred BALB C; Genomic Instability; fenotyp; Aging; Mice; zvířata; T-lymfocyty; Mice, Inbred C57BL; myši inbrední BALB C; klonální evoluce; T-Lymphocytes; antigeny; imunologická paměť